Migration of malleable penile prosthesis - Mohamed, Abdelrahman Yahya (Urol Ann, 2017)
Penile prosthesis migration is rare. Most reported cases are migration of inflatable penile prosthesis reservoirs. We reported a case of rectal migration of malleable penile prosthesis passed out as hard bowel motion without patient recognition.